Gambaran Strategi Pembelajaran Partisipatif pada Kegiatan Pembelajaran Bahasa Indonesia dalam Program Paket B di PKBM Tanjung Sari Kota Sawahlunto - Aldilla Hidayati; Setiawati Setiawati; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the activity of learning package B Indonesian language subjects get high score. This is thought to have something to do with the participatory learning strategy used by tutors. This study aims  to  describe  participatory  learning  strategies  by  tutors  in  B  package  program  of  Indonesian  subjects which include: (1) planning of learning activities, (2) implementation of learning activities, (3) evaluation of learning  activities.  This  type  of  research  is  descriptive  quantitative.  This  study  did  not  conduct  sampling, therefore the entire population was made a respondent. Data collection techniques used are questionnaires,  while  data  collection  tools  use questionnaires.  Data  analysis  techniques  using  the  formula  percentage. Suggestions  for  this  research,  so  that  participative  learning  strategies  can  be  improved  again  by  tutors  in learning Indonesian and other learning.